P01.035 Nivolumab and Temozolomide (TMZ) vs TMZ alone in newly diagnosed elderly patients (pts) with Glioblastoma (GBM) (NUTMEG): Trial in progress. (19th September 2018) - Khasraw, M; McDonald, K; Yip, S; Verhaak, R G; Heimberger, A B; Hall, M; Barnes, E; Hovey, E; Ellingson, B M; Lwin, Z
Abstract: Background: TMZ with short course radiotherapy (RT) is an option for elderly GBM patients. Nivolumab is a PD-1 inhibitor with known safety profile in GBM. An increase of mutations as we age is well documented in GBM and in cancer in general. A higher mutational load is associated with increased response to nivolumab. NUTMEG examines activity of nivolumab added to TMZ in GBM patients 65 years or older. Methods: NUTMEG patients will receive RT (40Gy/15 fractions) concurrently with TMZ 75mg/m2. Post-radiation, the experimental group will receive nivolumab (240 mg days 1 and 15 Q 28 days for cycles 1–4; then 480 mg day 1 Q 28 days for cycles 5–6) with adjuvant TMZ (150-200mg/m2 days 1–5 Q 28 days) for 6 cycles. The standard treatment group will receive same dose and schedule of TMZ. The primary endpoint is Overall Survival (OS). Secondary endpoints include: 6-month (mo) Progression Free Survival (PFS-6), adverse events using NCI CTCAE v4.03 incorporating immune related AEs, QoL (EORTC QLQ-30, BN-20, and EuroQol EQ-5D-5L), Neurologic Assessment in Neuro-Oncology (NANO) Scale and correlation between modified RANO and immune-related RANO in the experimental arm. Translational research (TR) endpoints include mutational burden deciphered by whole exome sequencing; immune-related markers PD-L1, CD3+, CD4+, CD8+ and FOXP3 tumour infiltrating lymphocytes (TILs) and correlation with clinical outcomes. Advanced MRI will assess distribution of perfusion and diffusion, 3D morphometric and texture features and pH-weighted imaging correlated with clinical and TR endpoints. Safety will be reviewed by an independent data safety monitoring committee. Assuming a median OS of 9 mo, and accrual of 18mo and ≥24 mo follow-up 102 patients will be randomized in a 2:1 allocation (68 in the experimental arm and 34 in the control arm). This randomized phase II design targets a hazard ratio (HR) TMZ + nivolumab: TMZ for survival between experimental and control arms with a 90% CI of HR/1.46 to HR*1.46. If the upper limit is less than 1, we would conclude TMZ + nivolumab to be superior to warrant further investigation. This phase II design may be converted to a larger phase III trial if, at the end of the study, the number of events is sufficiently large. Progress: At 28 May 2018, 5/18 study sites are open in Australia with 5 patients randomized. ACTRN12617000267358. Supported by NHMRC Project grant APP1125204 and Bristol-Myers Squibb.